NF-KappaB Pathway Is Involved in Bone Marrow Stromal Cell-Produced Pain Relief - Guo, Wei; Imai, Satoshi; Yang, Jia-Le; Zou, Shiping; Li, Huijuan; Xu, Huakun; Moudgil, Kamal D.; Dubner, Ronald; Wei, Feng; Ren, Ke (Frontiers in Integrative Neuroscience, 2018)
Bone marrow stromal cells (BMSCs) produce long-lasting attenuation of pain hypersensitivity. This effect involves BMSC’s ability to interact with the immune system and activation of the endogenous opioid receptors in the pain modulatory circuitry. The nuclear factor kappa B (NF-B) protein complex is a key transcription factor that regulates gene expression involved in immunity. We tested the hypothesis that the NF-B signaling plays a role in BMSC-induced pain relief. We focused on the rostral ventromedial medulla (RVM), a key structure in the descending pain modulatory pathway, that has been shown to play an important role in BMSC-produced antihyperalgesia. In Sprague Dawley rats with a ligation injury of the masseter muscle tendon (TL), BMSCs (1.5M/rat) from donor rats were infused i.v. at 1 w post-TL. P65 exhibited predominant neuronal localization in the RVM with scattered distribution in glial cells. At 1 w, but not 8 w after BMSC infusion, western blot and immunostaining showed that p65 of NF-B was significantly increased in the RVM. Given that chemokine signaling is critical to BMSCs’ pain-relieving effect, we further evaluated a role of chemokine signaling in p65 upregulation. Prior to infusion of BMSCs, we transduced BMSCs with Ccl4 shRNA, incubated BMSCs with RS 102895, a CCR2b antagonist, or maraviroc, a CCR5 antagonist. The antagonism of chemokines significantly reduced BMSC-induced upregulation of p65, suggesting that upregulation of p65 was related to BMSCs’ pain-relieving effect. We then tested the effect of a selective NF-B activation inhibitor, BAY 11-7082. The mechanical hyperalgesia of the rat was assessed with the von Frey method. In the pre-treatment experiment, BAY 11-7082 (2.5 and 25 pmol) was injected into the RVM at 2 h prior to BMSC infusion. Pretreatment with BAY 11-7082 attenuated BMSCs’ antihyperalgesia, but post-treatment at 5 w post-BMSC was not effective. On the contrary, in TL rats receiving BAY 11-7082 without BMSCs, TL-induced hyperalgesia was attenuated, consistent with dual roles of NF-κB in pain hypersensitivity and BMSC-produced pain relief. These results indicate that the NF-B signaling pathway in the descending circuitry is involved in initiation of BMSC-produced behavioural antihyperalgesia.